Sorption properties of wood impregnated with the fire retardant Burnblock - Miha Humar; Boštjan Lesar; Davor Kržišnik (Les)
The sorption properties of wood have a characteristic influence on some of its properties, such as the mechanical properties and susceptibility to fungal decay. Moist wood is more susceptible to fungal decay, and wood is often impregnated in order to protect it from fungal decomposition, photodegradation or fire. In particular, inorganic salts affect the sorption properties of wood. For this purpose, the sorption properties of Norway spruce wood impregnated with Burnblock refractory (uptake 38 kg/m³) were investigated. The microscopic analysis confirmed the presence of crystals of this in the cell lumina of wood tissue. Sorption properties were determined using an instrument capable of dynamic vapour sorption (DVS) assessment. DVS analysis confirmed that the sorption properties of impregnated spruce wood are comparable to those of non-impregnated spruce wood. However, the higher hysteresis at higher relative humidity is probably due to the presence of crystals in the cell lumina.